The Effect of Red Spinning Bottom on Increasing Hemoglobin Levels of Pregnant Women in Tanggabosi Village - Aryunita; Doriani Harahap (PT Inovasi Pratama Internasional, 2022)
Anemia in pregnancy is a major health problem in developing countries with high morbidity rates in pregnant women. Average pregnancies caused by anemia in Asia estimated at 72.6%. The high prevalence of anemia in pregnant women is a problem that is being faced by the Indonesian government. Anemia often occurs due to a lack of iron content in food, very low absorption of iron from food, the presence of substances that inhibits iron absorption. Iron anemia in pregnancy is a condition in which mothers with Hb levels below 11 grams/dL in the first and third trimesters and Hb levels less than 10.5 grams /dL in pregnancy. second trimester. This study aims to determine the effect of red spinach stew on increasing hemoglobin levels in pregnant women in the village of Tanggabosi II. The research method is a Quasi Experiment with a research design. One group pre test post test design. Samples were taken using rotary sampling. The number of samples was 20 pregnant women. Data analysis using Paired T Test. The results showed P = 0.000 (P <0.05). The conclusion is that there is an effect of red spinach stew on increasing hemoglobin levels in pregnant women.